The emergence and development of deconstruction in costume design - Yu. L. Gerasimova; N. O. Sosnina; O. Yu. Buleva; M. R. Timofeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article deals with deconstructionism as a postmodern stylistic movement during the second half of the 20th century, its embodiment in costume design, the reasons for the emergence of the concept of deconstruction in fashion, its main characteristics and attributes. Text analyses practices based on deconstruction, that were to appeared in fashion of different periods and in the creative concepts of designers during the period of the second half of the XX century and the beginning of the XXI century. Their formative and style-forming role is being reflected in the text. Particular attention is paid to an evolution of deconstruction as a creative method in costume design, its relevance in modern fashion